Vividness, Consciousness, and Mental Imagery Making the Missing Links across Disciplines and Methods - D'Angiulli, Amedeo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Today in many studies, mental images are still either treated as conscious by definition, or as empirical operations implicit to completing some type of task, such as the measurement of reaction time in mental rotation, an underlying mental image is assumed, but there is no direct determination of whether it is conscious or not. The vividness of mental images is a potentially helpful construct which may be suitable, as it may correspond to consciousness or aspects of the consciousness of images. In this context, a complicating factor seems to be the surprising variety in what is meant by the term vividness or how it is used or theorized. To fill some of the gaps, the goal of the present Special Issue is to create a publication outlet where authors can fully explore through sound research the missing theoretical and empirical links between vividness, consciousness and mental imagery across disciplines, neuroscience, psychology, philosophy, cognitive science, to mention the most obvious ones, as well as transdisciplinary methodological (single, combined, or multiple) approaches.